Welding Thermal Simulation and Metallurgical Characteristics Analysis in WAAM for 5CrNiMo Hot Forging Die Remanufacturing. (2017) - Hu, Zeqi; Qin, Xunpeng; Shao, Tan
Abstract: In order to analyze the performance of wire and arc additive manufacturing for 5CrNiMo hot forging die remanufacturing, the FEM numerical model of multi-layer and multi-pass welding was built. The thermal distribution and cycle in weld beads were investigated, and the simulation results conformed to the experimental measurements well. Then the microstructure and micro-hardness in different layers and the heat affected zone in the substrate was analyzed after the experiment of weld overlaying, and the influence of the thermal cycle on the metallurgical characteristics was also discussed. The results showed that the beads were affected by the preheating and the reheating of the previous and subsequent overlaying, and the grain size of the microstructure increased with the height of layers, while the micro-hardness decreased. Additionally, the difference of the structure between the adjacent layers was greater than that in the same layer.